Potential Integration of Geothermal Energy Resources and Coffee Plantation as a Geotourism Object - Eli Jamilah Mihardja; Arif Mulizar; Togu Pardede (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2022)
Geotourism concept utilizes all aspects of geology, with the scope of abiotic elements such as landscapes, rocks, minerals, fossils, soil, water, and processes, including geological history. In the Ulubelu area, there is potential for geothermal energy resources which is managed by Pertamina Geothermal Energy (PGE). In that area, there are already a Green Lake tourist destination and the potential of a coffee-plantation directly related to the community empowerment programs from PGE. Therefore, in an effort to optimize the program, research is carried out to study the potential of geotourism and destination branding strategies that can be carried out on the basis of a study of marketing- as well as environmental communications. The research was conducted in Ulubelu from July to November 2022, using the case study method. The results of the temporary study produce preliminary data that there is potential to integrate the existence of geothermal energy and coffee-plantation to be formed as geotourism objects through community-based tourism (CBT) model.